2020
DOI: 10.1002/nbm.4216
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of recovery after spinal cord injury with behavioral measures and diffusion, quantitative magnetization transfer and functional magnetic resonance imaging

Abstract: Spinal cord injuries (SCIs) are a leading cause of disability and can severely impact the quality of life. However, to date, the processes of spontaneous repair of damaged spinal cord remain incompletely understood, partly due to a lack of appropriate longitudinal tracking methods. Noninvasive, multiparametric magnetic resonance imaging (MRI) provides potential biomarkers for the comprehensive evaluation of spontaneous repair after SCI. In this study in rats, a clinically relevant contusion injury was introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
(95 reference statements)
3
14
0
Order By: Relevance
“…Our MRI results on lesional volumes were similar to a recent diffusion MRI study of contusion SCI at the lumbar level, where pool size ratio measurements derived from quantitative magnetization transfer, indicative of myelination, progressively decreased at the injury epicenter and adjoining areas within 2 weeks after SCI (Wu et al 2020). However, the pool size ratio changes had no association with sensory and motor behavioral outcomes (Wu et al, 2020). These results indicate that the nonlesional spinal cord may harbor the bulk of the reorganization related to motor circuits during the subacute and chronic phases after SCI.…”
Section: Spinal Pathophysiology Underlying Lesional and Nonlesional Morphometric Parameters Is Coupledsupporting
confidence: 86%
See 1 more Smart Citation
“…Our MRI results on lesional volumes were similar to a recent diffusion MRI study of contusion SCI at the lumbar level, where pool size ratio measurements derived from quantitative magnetization transfer, indicative of myelination, progressively decreased at the injury epicenter and adjoining areas within 2 weeks after SCI (Wu et al 2020). However, the pool size ratio changes had no association with sensory and motor behavioral outcomes (Wu et al, 2020). These results indicate that the nonlesional spinal cord may harbor the bulk of the reorganization related to motor circuits during the subacute and chronic phases after SCI.…”
Section: Spinal Pathophysiology Underlying Lesional and Nonlesional Morphometric Parameters Is Coupledsupporting
confidence: 86%
“…compared with spinal volumetric changes after SCI. Our MRI results on lesional volumes were similar to a recent diffusion MRI study of contusion SCI at the lumbar level, where pool size ratio measurements derived from quantitative magnetization transfer, indicative of myelination, progressively decreased at the injury epicenter and adjoining areas within 2 weeks after SCI (Wu et al 2020). However, the pool size ratio changes had no association with sensory and motor behavioral outcomes (Wu et al, 2020).…”
Section: Spinal Pathophysiology Underlying Lesional and Nonlesional Morphometric Parameters Is Coupledsupporting
confidence: 85%
“…Recent preclinical investigations have included a combination of MT imaging and diffusion MRI. 20,25,49 Moreover, the findings in this study will complement a recent test-retest reproducibility study in advanced diffusion MRI techniques in mice at 9.4 T. 35…”
Section: Discussionsupporting
confidence: 54%
“…There is strong interest in applying MT to preclinical rodent neuroimaging studies at ultra-high field strengths, demonstrated by MTR 1922 and qMT studies. 13,2325 The feasibility of MTsat in mice at 9.4 T has been shown previously 26 and MTsat has been explored in a feline model of demyelination at 3 T. 27 Although most MTsat studies have been performed at 3 T, recently, Olsson et al reported an optimized whole-brain MTsat protocol at 7 T, 28 which highlights the increasing interest in this method. In vivo studies of MTsat in humans at 3 T have shown high reproducibility.…”
Section: Introductionmentioning
confidence: 93%
“…These interactive and dynamic processes are not well understood, partially due to the lack of suitable monitoring tools. Non-invasive, multi-parametric, magnetic resonance imaging (mpMRI) methods allow detection and monitoring of the injury itself as well as injury-associated structural, functional and molecular changes over time ( Stroman et al, 2014 , Wheeler-Kingshott et al, 2014 , Chen et al, 2015 , Wang et al, 2015 , Wang et al, 2016b , Wang et al, 2018b , Wang et al, 2019 , Yang et al, 2015 , Wu et al, 2020 ). In previous studies, we have studied injured spinal cords of non-human primates (NHPs) using a mpMRI protocol, including chemical exchange saturation transfer (CEST) ( Wang et al, 2015 , Wang et al, 2018b ), relayed nuclear Overhauser enhancement (NOE) ( Wang et al, 2015 , Wang et al, 2018b ), diffusion tensor imaging (DTI) ( Wang et al, 2015 , Mishra et al, 2020 ), quantitative magnetization transfer (qMT) ( Wang et al, 2016b , Wang et al, 2019 ), and functional MRI (fMRI) ( Chen et al, 2015 , Yang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%